Hotel web design for marketing purpose / Muhammad Sufian Yusof - Yusof, Muhammad Sufian (2008)
Today's world of globalization creates the opportunity for e-commerce as a huge marketing opportunity with the boundary-less market. Hotel industry is one of the industries that have been affected with the growth of internet user through online reservation. Therefore, a web presence is required for the hotels that want to enter the new market. However, a strong web presence is required to make the website really effective in creating online revenue. Thus, the hotel web marketing principles is the key to help hoteliers improve their online revenue. The objective of this research is to redesign a hotel website using hotel web marketing principles and to identify the effectiveness of the implementation of hotel website using the principles. The results indicate that the implementation of the hotel web marketing principles can boost up page visits, Search Engine Optimization that makes the hotel more marketable. The result also indicates that the new redesigned hotel also has entered the main marketing channel that is search engine. This thesis also provides several recommendations in order to improve hotel web marketing and for a better research in the future.